Risorgimento i Francesco Nullo .......... 25 - Kiwior-Filo, Małgorzata (Riflessioni intorno alla storia politica d’Italia = Refleksje wokół historii politycznej Włoch, 2025)
RISORGIMENTO AND FRANCESCO NULLOThe article explores the shared ideals and independence movements of Poland and Italy in the 19th century, presenting the Risorgimento not only as the process of Italian unification but also as a manifestation of the universal struggle for freedom and national identity. Special focus is given to Francesco Nullo, the Italian patriot who died in 1863 during the January Uprising in Poland. The text examines traditions of solidarity among oppressed nations, mutual ideological influences, the role of the Great Emigration, and initiatives such as Mickiewicz’s Legion and the Polish Military School in Genoa. The symbolic dimension of Nullo’s sacrifice is highlighted as a lasting emblem of brotherhood in arms and reciprocal gratitude between Poland and Italy.